Influence of weather factors and management of Septoria leaf spot of tomato in sub-tropics - V.K. RAZDAN, P.K. RAINA* (Indian Phytopathology, 2010)
Studies conducted on the effect of weather factors on seasonal occurrence of Septoria lycopersici indicate that relative humidity coupled with rainy days/percentage of total rainfall elicit maximum disease build up. Only two varieties (S-12 and SH-12) out of 41 cultivars screened for disease resistance against Septoria leaf spot, showed resistance at each test locations (R.S. Pura and Paunichak). Spraying the tomato crop with Dithane Z-78 or Dithane M-45 at 0.2% each, proved highly efficacious in restricting the disease spread under field conditions and thereby stabilizing the yield returns.